T-cell engaging poly(lactic-co-glycolic acid) nanoparticles as a modular platform to induce a potent cytotoxic immunogenic response against PD-L1 overexpressing cancer. (December 2022) - Duwa, Ramesh; Pokhrel, Ram Hari; Banstola, Asmita; Pandit, Mahesh; Shrestha, Prakash; Jeong, Jee-Heon; Chang, Jae-Hoon; Yook, Simmyung
Abstract: Bispecific nanoparticles (NPs) are conjugated with two antibodies that enhance T cell cytotoxicity by sequentially targeting CD3 and tumor-specific proteins. This interaction redirects T cells to specific tumor antigens and activates them to lyse tumor cells by blocking two different signaling pathways simultaneously. This study developed NP-based bispecific T-cell engagers (nanoBiTEs), which are R848-loaded bispecific poly(lactic- co -glycolic acid) NPs decorated with anti -CD3 antibody targeting T cells and anti -PD-L1 antibody targeting PD-L1 ligands (bis-R848-PLGA-NPs). Bis-R848-PLGA-NPs enhance the immunogenic response in destroying cancer cells by restoring the T cell effector functions. These interactions allow T cells to come in close proximity to the tumor cells. Finally, the release of R848 from PLGA-NPs activates dendritic cells, enhancing T cell activation. In vitro results show maximum internalization of bis-R848-PLGA-NPs in SK-OV3 and B16F10 cell lines, attributed to high PD-L1 expression in both cells. Furthermore, bis-R848-PLGA-NPs-treated CD8 + T cells exhibit a significantly increased total amount of CD8 + /CD25 +, CD8 + /CD69 +, and cytokine expression that leads to the robust inhibition of PD-L1 expressed cancer cells. Additionally, tumor growth is significantly inhibited by bis-R848-PLGA-NPs in the B16F10 xenograft mouse model and significantly enhanced intratumoral infiltration of CD4 + and CD8 + T cells, as well as tumor-infiltrated cytokines.